Post-Operative Haemodynamic Monitoring of Patients undergoing Corrective Open Heart Surgery for Structural Heart Defects - Ibrahim, Hanan Mohamed; Eldin Mansor, Mervat Gamal; Kamel, Waleed Ismail; Salah El Din Soliman, Nanies Mohamed; El Din Abo El Wafa, Mohamed Salah; Bakry, Nehad Ahmed (International Journal of Child Health and Nutrition, 2025)
Background: Accurate hemodynamic monitoring is essential when identifying and treating critically ill pediatric patients. Effective perioperative care directed by sophisticated hemodynamic monitoring can lower problems and enhance results, even though the best monitoring method is still up for debate. Objective: to compare monitoring methods of cardiac output and systemic hemodynamics post-cardiac surgery and its correlation to the clinical status of patients (reflected by clinical signs and laboratory assessment) and outcome, focusing on non-invasive cardiometry and echocardiography. Methodology: A cross-sectional study was conducted on 40 pediatric patients under five years old who underwent corrective cardiac surgery for congenital heart lesions. Hemodynamic parameters were assessed using echocardiography and ICON, alongside clinical evaluation and biomarkers (BNP and lactate), at 6 and 24 hours postoperatively. Statistical analysis was employed to identify significant correlations and trends. Results: Significant hemodynamic changes were observed in the immediate post-operative period. Clinical assessment detected low cardiac output in 47% of patients at 6 hours, decreasing to 45% at 24 hours. TAPSE and ejection fraction, measured via echocardiography, showed significant correlations with clinical signs of low cardiac output at 6 and 24 hours, respectively. ICON parameters, such as thoracic fluid content (TFC), demonstrated significant trends, correlating with fluid balance and time on bypass. However, ICON lacked the precision of echocardiography for certain measures; its continuous, non-invasive monitoring provided valuable insights into hemodynamic trends. Conclusion: Hemodynamic monitoring post-operative cardiac surgery with early management of instability decreases the risk of complications and prolonged hospital stay. Clinical assessment of low cardiac output symptoms is crucial in the hemodynamic monitoring of patients, paying attention to vital data. Echocardiography and electrical cardiometry parameters have significant correlations with each other, including contractility (TAPSE, CI) and fluid assessment values (IVC collapsibility and TFC). BNP levels are best used not as a "stand-alone" test but in conjunction with existing multivariable risk indexes.